Prevalence and comparison of depression rates in geriatric patients of old age home and community, and its association with chosen demographic factors - Singh, Preksha T.; Singhvi, Shreyans D.; Bhandari, Gautam (International Journal of Research in Medical Sciences, 2020)
Background: Depression is an emerging mental health condition and elderly population of the world is often affected by it. In the elderly, it often goes unnoticed and often burdens them. Methods: Two groups of population one from an old age home and the other from a community were selected. Data was collected using a Geriatric Depression Scale (GDS) and a demographic form. The data was compiled and analyzed using Google Spreadsheets. Results: Depression rates were found in both, the old age home and the community. The rates were found higher in the old age home than the community. The demographic factors chronic illness, gender, educational status and marital status were found to be associated with depression. Conclusions: As depression in elderly is a fairly common phenomenon, it should be paid more attention. The elderly should receive intervention for the disease and be able to sustain it.